PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP EFEKTIFITAS KERJA TENAGA PENGAJAR PKBM DI KABUPATEN BOGOR - Nurdiansyah; Adrian Adha (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study is motivated by the importance of improving the work effectiveness of PKBM teaching staff through education and training programs. The study aims to analyze the effect of education and training on the work effectiveness of PKBM teaching staff in Bogor Regency, both partially and simultaneously. The research employed a quantitative method with a survey approach using questionnaires distributed to 33 respondents. The collected data were analyzed using SPSS through multiple linear regression, t-tests, and F-tests. The findings indicate that education has a positive and significant effect on work effectiveness, with a significance value of 0.002. Likewise, training also demonstrates a positive and significant influence, with a significance value of 0.000. Simultaneously, education and training significantly affect work effectiveness, as indicated by an F-value of 25.67 and a significance level of 0.000. Furthermore, the coefficient of determination (R²) value of 0.62 reveals that 62% of work effectiveness can be explained by the education and training variables. Based on these findings, it can be concluded that education and training have a significant influence on the work effectiveness of PKBM teaching staff in Bogor Regency. Therefore, improving the quality of education and implementing continuous training programs are essential to enhance the work effectiveness of teaching personnel.